Comparative Study among Composite Breads Incorporated with Full Fatted and Defatted Rice Bran (Journal of Environmental Science and Natural Resources, 2019)
Rice bran, a milling byproduct of rice is rich in nutrients especially high in fiber and protein in comparison with white wheat flour-which is predominantly used for bread production. Inclusion of rice bran with wheat flour was expected to induce nutritional value of bread positively. Two form of rice bran sample both full fatted and defatted were incorporated with wheat flour in a proportion of 0%, 5%, 10% and 15% respectively to develop composite bread. Physical, chemical, and sensory evaluation was carried out to determine the quality of different composite breads. Bread weight didn’t differ statistically though there was a marginal declination of volume for bread with the increase of the percentage of rice bran. The percentage of protein and fiber was increased rationally as expected. A level of 10% rice bran added to bread was regarded to yield good sensory quality.J. Environ. Sci. & Natural Resources, 11(1-2): 43-52 2018